(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Zootoponyms have significant influence on geographic names of Kazakhstan, it is an indicator of national memory, identity and tribute to nomadic past of Kazakhs. Each one of these names carry certain information in «open» form and in «convoluted» / «encrypted» form. This article is devoted to the study of traditional zootoponyms in geographic names, which reflected the pagan beliefs, totemic representations and especially the mental consciousness of Kazakh nomads. Observations were made on contextual conceptualization and schematization of images of domestic and wild animals in zootoponymic verbal manifestations. Key words: zootoponyms, Kazakhstan, nomadic past, tribute, toponymic legends.